2017
DOI: 10.1039/c7cp04686c
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic effects at the Cu2O2 core – a density functional theory study

Abstract: This work presents for the first time the impact of relativistic effects on the CuO peroxide dicopper(ii)-bis(μ-oxo) dicopper (iii) equilibrium bonding motif in existing tyrosinase model complexes [Cu(btmgp)(μ-O)] and [Cu{HC(tBuPz)Py}(O)] [S. Herres et al., Inorg. Chim. Acta, 2005, 358, 1089; S. Herres-Pawlis et al., Eur. J. Inorg. Chem., 2005, 3815; A. Hoffmann et al., Angew. Chem., Int. Ed., 2013, 52, 5398]. We use density functional theory (TPSSh/cc-pVTZ+D3BJ) with various relativistic approaches (ECPs, DKH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Furthermore, the use of ECPs is an inexpensive way of accounting for relativistic effects since the fixed core potentials have been optimized to include relativistic effects. 37 It has been found that the scalar relativistic effects in ECPs can give similar results as the relativistic allelectron calculations when analyzing ground-state (MSPA) properties. 23 All starting geometries and multiplicities of the bare nanoparticles were adopted from Chaves et al 38 and were obtained with the all-electron full-potential Fritz Haber institute ab initio molecular simulations (FHI-aims) package 39,40 using the PBE functional and the tight_tier1 basis set for geometry optimization.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the use of ECPs is an inexpensive way of accounting for relativistic effects since the fixed core potentials have been optimized to include relativistic effects. 37 It has been found that the scalar relativistic effects in ECPs can give similar results as the relativistic allelectron calculations when analyzing ground-state (MSPA) properties. 23 All starting geometries and multiplicities of the bare nanoparticles were adopted from Chaves et al 38 and were obtained with the all-electron full-potential Fritz Haber institute ab initio molecular simulations (FHI-aims) package 39,40 using the PBE functional and the tight_tier1 basis set for geometry optimization.…”
Section: Methodsmentioning
confidence: 89%
“…In addition, the hybrid meta-GGA functional TPSSh and a triple-zeta basis set with polarization functions have shown better performance in the optimization of ground-state structures and provide improved results for energies of transition-metal complexes of various spin and oxidation states compared to other evaluated functionals. , The Def2-TZVP comprises effective core potentials (ECPs) for 4d and 5d metals and provides a good balance between accuracy and computational cost. Furthermore, the use of ECPs is an inexpensive way of accounting for relativistic effects since the fixed core potentials have been optimized to include relativistic effects . It has been found that the scalar relativistic effects in ECPs can give similar results as the relativistic all-electron calculations when analyzing ground-state (MSPA) properties …”
Section: Computational Methodsmentioning
confidence: 99%
“…However, several low-lying isomers may coexist, depending on the ligands coordinated to two copper atoms. Previous studies have demonstrated that the electronic structures of these systems have strong multireference characters, and the evaluation of the relative energies among different isomeric species is quite challenging for many theoretical methods. ,, Here we are interested in the relative energy between two isomers of a di-copper–oxygen–ammonia complex, labeled as bis and per , as shown in Figure . The relative energies of these two isomers have been investigated by many theoretical methods. , Here we will first investigate whether the use of the initial GVB orbitals constructed with our procedure can lead to the converged GVB energies for two isomers.…”
Section: Resultsmentioning
confidence: 99%
“…The Cartesian cc-pVTZ basis set is employed for Cu and O atoms and cc-pVDZ for N and H atoms. Relativistic effects are not considered, although there is indication that they may play an important role in these two species. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation